Hubungan Karakteristik Individu, Kondisi Pekerjaan Dan Lingkungan Kerja Dengan Stres Kerja Pada Guru Di SDN Meruya Utara 13, Kembangan, Jakarta Barat Tahun 2023 - Syafitri, Dini; Saiful Bahri, Beben; Pramono, Budi; Anastasia Febriani, Susana (CV. Multi Kreasi Media, 2024)
Teachers will spend most of their time at work, namely at school by doing the same tasks every day. Therefore, the condition of the school's physical environment must meet the requirements that aim not to cause teachers to experience work stress. Work stress is a state of tension that causes physical and psychological imbalances, which have an impact on emotions, thought processes, and employee conditions. Job stress in teachers can occur not only from one causal factor, but from a variety of causal factors, both internal and external. This study aims to determine